ANALISIS QUALITY OF SERVICE (QOS) VIDEO CONFERENCE PADA JARINGAN INTERNET DENGAN MENGGUNAKAN AKSES WIMAX (WORLD WIDE INTEROPERABILITY FOR MICROWAVE ACCESS) - ., Arif Surahman (Faculty of Engineering, Universitas Tanjungpura, 2017)
Video conferencing is a system that allows two or more people in different places to communicate with each other by displaying images / videos of their interlocutors. The system is one of the results of the development in the multimedia world is currently becoming a new trend in the world of telecommunications. In this Final Project, the video conference system is designed and implemented in the office of PT. Aplikanusa Lintasarta Jl. Sukajaya. Pontianak as the sender side and the destination location is in Gg. Cahaya Baru as the receiving side. Video conferencing is done with a face to face system and uses only one user on WiMAX access. The Video Conference app uses the Skype app. The focus of this research is QoS analysis on Video Conference service with bandwidth of 512 Kbps and 64 Kbps. From the results of testing and analysis of system performance, obtained that the video and audio quality obtained quite acceptable. The maximum value of QoS parameters that can be accepted on 512 Kbps bandwidth is the delay value of 13.1 ms, 0.11 ms jitter, 0% packet loss, 100% troughput with TIPHON 3.75 standard (good) while with 64 Kbps bandwidth obtained 154,22 ms delay, jitter 39.97 ms, packet loss 10%, troughput 81.05% with standard TIPHON 2.75 (medium). So it can be concluded that this system can function properly. Key words: Quality of Service (QoS), delay, jitter, packet loss, troughput